Pengaruh Lingkungan Kerja dan Kerja Sama Tim terhadap Peningkatan Kinerja Karyawan Divisi Administrasi PT Rick Auto - Dwi Ela Rahmawati; Musthafa Kamil (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
The work environment and teamwork are factors that play a role in improving employee performance, especially in the administration division which has a crucial role in supporting the smooth operation of the company. Unsupportive work environment conditions and suboptimal teamwork can have an impact on declining employee performance. Therefore, this study aims to determine the effect of the work environment and teamwork on improving the performance of employees in the administration division of PT Rick Auto. The method used is a quantitative method with a data collection technique through distributing questionnaires to all employees of the administration division of PT Rick Auto as many as 60 respondents using a saturated sampling technique. Data analysis was carried out using SPSS version 26 through multiple linear regression tests, t-tests, f-tests, and coefficient of determination tests. The results of the study indicate that partially the work environment does not have a significant effect on improving employee performance, while teamwork has a positive and significant effect on improving employee performance. Simultaneously, the work environment and teamwork have a significant effect on improving employee performance in the administration division of PT Rick Auto.